Hambatan Aksesibilitas Masyarakat terhadap Hak Keadilan Perdata - Rizky Wirastomo; Fajri Matahati Muhammadin; Tata Wijayanta (Fakultas Hukum Universitas Islam Indonesia, 2011)
Right to seek adjudication of conflicts qualifies as human rights. However, we find that whenever the economical value of a dispute is insignificant in comparison towards court’s fees, this rights tend to be infringed. Judicial reform with a sole interest of a faithful recognition of human rights is needed.